Investigating possible kinetic limitations to MgB2 hydrogenation. (29th November 2019) - Liu, Y.-S.; Klebanoff, L.E.; Wijeratne, P.; Cowgill, D.F.; Stavila, V.; Heo, T.W.; Kang, S.; Baker, A.A.; Lee, J.R.I.; Mattox, T.M.; Ray, K.G.; Sugar, J.D.; et al.
Abstract: An investigation is reported of possible kinetic limitations to MgB2 hydrogenation. The role of H–H bond breaking, a necessary first step in the hydrogenation process, is assessed for bulk MgB2, ball-milled MgB2, as well as MgB2 mixed with Pd, Fe and TiF3 additives. The Pd and Fe additives in the MgB2 material exist as dispersed metallic particles in the size range 5–40 nm diameter. In contrast, TiF3 reacts with MgB2 to form Ti metal, elemental B and MgF2, with the Ti and the MgF2 phases proximate to each other and coating the MgB2 particulates with a film of thickness 3 nm. Sieverts studies of hydrogenation kinetics are reported and compared to the rate of H–H bond breaking as measured by H-D exchange studies. The results show that H–H bond dissociation does not limit the rate of hydrogenation of MgB2 because H–H bond cleavage occurs rapidly compared to the initial MgB2 hydrogenation. The results also show that surface diffusion of hydrogen atoms cannot be a limiting factor for MgB2 hydrogenation. Instead, it is speculated that it is the intrinsic stability of the B–B extended hexagonal ring structure in MgB2 that hinders the hydrogenation of this material. This supposition is supported by B K-edge x-ray absorption measurements of the materials, which showed spectroscopically that the B–B ring was intact in the material systems studied. The TiF3 /MgB2 system was examined further theoretically with reaction thermodynamics and phase nucleation kinetic calculations to better understand the production of Ti metal when TiB2 is thermodynamically favored. The results show that there exist physically reasonable ranges for which nucleation kinetics supersede thermodynamics in determining the reactive pathway for the TiF3 /MgB2 system and perhaps for other additive systems as well.